KAJI KARAKTERISTIK PERPINDAHAN PANAS PENGARUH BELOKAN TAJAM PADA PENUKAR KALOR TIPE TUBE - Zulfan Zulfan; Ahmad Syuhada; Zahrul Fuadi; Al Munawir (universitas teuku umar, 2020)
Using the thermal machines in the production process or overdone heat power operation require unit of Heat Exchanger (HE) having high level heat transfer coefficient (hc) for transferring to the thermal reservoir. Experimental studies have been done for heat transfer characteristics of forced convection on the round duct with method use that compare three of heat exchanger with a variety of pipe bends and a long pass after a turn that is different. HE pipes have length of tube 500 mm with a 12 bends, HE pipes length of tube 250 mm with 24 bends and HE pipes length of tube 125 mm with 48 bends. The heat fluid flowed into the tube, and the tube is immersed in the cold water tank. For each of test equipments can be done three times experiment with different variations in inlet temperature that is at 600C, 700C and 800C, with a duration of 5 minute intervals for 50 minutes. Many pipe bends and short passes after a HE will increase turbulence flow pattern. The high of turbulence will increase the value of heat transfer coefficient, but it can hold on fluid flow rate. Keywords : heat transfer characteristics, round duct, sharp bends, long pass